1983
DOI: 10.1111/j.1442-9071.1983.tb01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Findings Among One Thousand Inhabitants of Rarotonga, Cook Islands

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
(1 reference statement)
0
12
0
Order By: Relevance
“…32 Table 5 presents the prevalence of DR in various types of diabetic populations. 7,8,10,[33][34][35][36][37][38][39][40][41][42] In addition to differences in the diagnostic criteria, this disparity is largely due to the different sources of type 2 diabetes. Since subjects with DR in our study were identified among presymptomatic type 2 diabetic patients, a substantial proportion of patients had NPDR, and only a small proportion of diabetic patients had severe DR.…”
Section: Prevalence Of Diabetic Retinopathymentioning
confidence: 99%
“…32 Table 5 presents the prevalence of DR in various types of diabetic populations. 7,8,10,[33][34][35][36][37][38][39][40][41][42] In addition to differences in the diagnostic criteria, this disparity is largely due to the different sources of type 2 diabetes. Since subjects with DR in our study were identified among presymptomatic type 2 diabetic patients, a substantial proportion of patients had NPDR, and only a small proportion of diabetic patients had severe DR.…”
Section: Prevalence Of Diabetic Retinopathymentioning
confidence: 99%
“…The prevalence of both diabetic retinopathy (DR) (3) and nephropathy (9) is high in the Micronesians of Nauru, which has one of the highest recorded prevalences of NIDDM, but retinopathy was relatively uncommon in Polynesians in the Cook Islands (10).…”
mentioning
confidence: 99%
“…13 Such primary and secondary prevention strategies are believed to be costeffective. 14 The prevalence of diabetic retinopathy has been reported for a few Pacific nations, ranging from 8.2% to 52.6%, [15][16][17][18] but in the last ophthalmic survey in Vanuatu (1989), of 3520 people aged .6 years, diabetic retinopathy was not identified as a major cause of blindness or low vision. 19 There have been no recent studies on the prevalence of non-communicable diseases or on the prevalence of diabetic retinopathy in Vanuatu.…”
mentioning
confidence: 99%